POLITENESS STRATEGIES IN BATAK KARO LANGUAGE (A PRAGMATIC ANALYSIS) (Krinok:Jurnal Linguistik Budaya, 2022)
The purpose of this research is to identify types of politeness strategies andthen to describe the function of politeness strategies in Batak Karo language especially in Perbesi village, Tiga Binanga Sub-district, Tanah Karo Regency, North Sumatera province. This research was conducted by using descriptive qualitative method theory by Lincoln and Guba (1985:424) and it is also strongly supported by Creswell (2014:171), the researcher uses Non Participant Observational Method (SBLC) to collecting the data. The data were analyzed by using referential method, the researcher also uses an informal and formal method to represent the results of the analysis.The result of the research reveals some findings showed that the Karonese families used four types of politeness strategies, there are: (1) Bald on Record Strategy, (2) Positive Politeness Strategy, (3) Negative Politeness Strategy, and (4) Off Record Strategy both interactions: Karonese families in North Sumatera Province, Tanah Karo Regency, Tiga Binanga sub district, especially at Perbesi village. Based on 28 data found in this research, the researcher found 19 data or 67.9% data used Positive Politeness Strategy, 4 data or 14.2% data used Negative Politeness Strategy, 3 data or 10.7% data used Bald on Record Strategy, and the last 2 data or 7.2% data used Off Record Strategy. The most dominant Politeness Strategies used in Karonese language at Perbesi village, Tiga Binanga Sub-district, Tanah Karo Regency, North Sumatera Province is Positive Politeness Strategies, with the percentage 67.9%, the types of politeness strategies proposed By Brown and Levinson theory (1987:101). The researcher found the most dominant functions of politeness strategies is Commisive functions of politeness strategy, with 11 data (39.3%). The Karonese used Commisive function strategy more than others functions. The second highest frequency is Directive function of politeness strategy, with 7 data (25%), the third is Representative function, with 6 data (21.4%) and then Expressive function of politeness, with 4 data (14.3%), there is no Declaration function that used by Karonese Families at the time. Therefore, based on the research, the researcher formulated the highest frequency of the politeness strategy in Batak Karo Language is achieved by the Commisive Function, the function of politeness proposed By Searle theory (1983:240).